2018
DOI: 10.1007/s40259-018-0324-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Management of Chimeric Antigen Receptor T-Cell Therapy-Related Toxicities

Abstract: Chimeric antigen receptor T-cell (CAR-T) therapy has proven to be a very effective cancer immunotherapy. Axicabtagene ciloleucel and Tisagenlecleucel are the first in class anti-CD19 CART cells currently available for relapsed-refractory adult large B-cell lymphoma. Tisagenlecleucel is also available for pediatric and young adult (up to age 25) patients with relapsed-refractory B-acute lymphoblastic leukemia. Cytokine release syndrome (CRS) and CAR T-cell associated encephalopathy syndrome (neurotoxicity) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 69 publications
0
54
0
Order By: Relevance
“…Cytokine Target Clinical effect Reference Tocilizumab IL-6 Block Il-6 receptor, and revert the cytokine storm production Luo et al [84] Xu et al [95] Dholaria et al [96] Zhang et al [ [44]. SARS-CoV-2 appears to act on the activation and maturation of IL-1β, which in turn activates other proinflammatory cytokines, such as IL-6 and TNF-α [45][46][47].…”
Section: Covid19 Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokine Target Clinical effect Reference Tocilizumab IL-6 Block Il-6 receptor, and revert the cytokine storm production Luo et al [84] Xu et al [95] Dholaria et al [96] Zhang et al [ [44]. SARS-CoV-2 appears to act on the activation and maturation of IL-1β, which in turn activates other proinflammatory cytokines, such as IL-6 and TNF-α [45][46][47].…”
Section: Covid19 Treatmentmentioning
confidence: 99%
“…The cytokine storm, including elevated levels of IL-6, has also been associated with cardiac damage in these patients [94]. With regard to the important role of IL-6 in the SARS-CoV-2-induced cytokine storm and its evasion, it has been reported that the monoclonal antibody tocilizumab acts by blocking the receptor of IL-6 and has been reported to reverse cytokine hyperproduction [84,[95][96][97], inflammation, and pulmonary fibrosis [98,99]. In fact, a multicenter clinical trial is under way in China on the usefulness of tocilizumab to treat patients with COVID-19 (NCT04252664 & NCT04257656), and it has already been included in clinical practice guidelines in China and Italy [100,101].…”
Section: L-6mentioning
confidence: 99%
“…Anti-IL-6 agents are a class of drugs with anti-inflammatory properties that act by targeting either the IL6 receptor or IL-6 itself. Studies have shown that tocilizumab, an IL-6 receptor antibody, could reverse CRS in the setting of chimeric antigen receptor T-cell therapy for cancer [36]. Because of the greatly elevated serum levels of IL-6 in patients with COVID-19 [3], its off-label used in the early stage of the diseases suggests a favorable impact on the course of COVID-19 [37].…”
Section: Cytokine-targeting Therapiesmentioning
confidence: 99%
“…CAR T cell therapy can cause severe cytokine release syndrome (CRS), or a characteristic immune cell-associated neurologic syndrome (ICANS). Both are associated with significant morbidity and mortality [36][37][38] , and are characterized by high levels of inflammatory cytokines and, to a lesser extent, by high numbers of CAR T cells in the blood 6 . Both forms of toxicity occur in predictable distributions across patient populations 39 .…”
Section: Discussionmentioning
confidence: 99%